A Systematic Literature Review of the Digital Orientation of MSMEs - Rayyan Sugangga; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardana (International Journal of Economics and Management Research, 2023)
. Digital orientation is included in the important capabilities that need to be possessed for the development of MSMEs. This needs to be supported by a focus on digital strategies to answer obstacles such as the lack of digital orientation and the lack of human resource capabilities to utilize information technology. This research uses a Systematic Literature Review approach, to answer about the concept of digital orientation, the development of research related to digital orientation and topics or variables related to digital orientation. The results found that research on the topic of digital orientation has only accelerated in 2020 and indeed digital orientation has an influence on MSME business processes.